Penetapan Status Tersangka Dan Terdakwa Calon Kepala Daerah Dan Implikasi Yuridisnya Dalam Pemilihan Kepala Daerah (Kajian Yuridis Normatif) - Imam Ropii (Faculty of Law, Universitas Pattimura, 2017)
Political contestation in the election of regional heads simultaneously in the third stage of 2017 became popular in particular the election of regional heads in Jakarta Special Capital Region (DKI). The popularity of DKI Regional Head election is because one of the candidates of the regional head (petahana candidate) is currently a suspect status and has even increased to be the defendant for allegedly doing the act of defamation of religion. The juridical of the candidate for the head of a suspect or defendant has no effect on the nomination process in the election. Couple of candidates with such status will continue to follow the election stage to complete. If in the Pilkada the suspect's partner or the defendant wins, the convicted person will be dismissed and subsequently replaced as stipulated in the legislation.